2020
DOI: 10.1021/acs.inorgchem.0c03095
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboidal Pt(II) Metallacycle-Based Hybrid Viral Nanoparticles for Cell Imaging

Abstract: Supramolecular coordination complexes (SCCs) have emerged as anticancer agents. Tracking the movement of these metallic anticancer agents plays an important role in the field of biomedicines. Herein, we describe a method for tracking the movement of a rhomboidal Pt(II) metallacycle agent using the quantum dots encapsidation in vitro self-assembly system of viral proteins. When incubated with living Vero cells, self-assembly of hybrid viral nanoparticles were employed for simultaneous cell imaging and visual tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Malignant tumor, one of the deadliest diseases in the world, threatens the health of human beings necessitating uninterrupted effort toward the accurate controlled diagnosis and therapeutic strategy of cancer, conversely, promoting the development of high precise, and high efficiency technology in the clinic. Recently, the optical method attracts significant attention due to its capability to offer noninvasive, high spatial resolution and the ability to provide physiological and pathological information for diverse biomedical applications [1][2][3]. Nevertheless, the traditional optical technology based on UV or Vis light prevents further development owing to its low absorption and scattering, reduced background autofluorescence interaction by the tissue [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumor, one of the deadliest diseases in the world, threatens the health of human beings necessitating uninterrupted effort toward the accurate controlled diagnosis and therapeutic strategy of cancer, conversely, promoting the development of high precise, and high efficiency technology in the clinic. Recently, the optical method attracts significant attention due to its capability to offer noninvasive, high spatial resolution and the ability to provide physiological and pathological information for diverse biomedical applications [1][2][3]. Nevertheless, the traditional optical technology based on UV or Vis light prevents further development owing to its low absorption and scattering, reduced background autofluorescence interaction by the tissue [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating the thermodynamic parameters might help provide clues on the involvement of these forces in the conjugation process. According to the view of Ross ( Jiang et al, 2019 ; Li et al, 2020 ; Shi et al, 2021 ), when Δ H θ < 0 and Δ S θ < 0 were associated with hydrogen bonding or van der Waals forces, the negative values obtained for both Δ H θ (−4.428 × 10 4 J·mol −1 ) and Δ S θ (−1.144 × 10 2 J·mol −1 K −1 ) in this study suggested the involvement of hydrogen bonding or van der Waals forces in the formation of Pb 2+ and CIZS QDs. The negative enthalpy change is due to the broken Pb 2+ -H 2 O bond, which is favorable for the formation of the Pb 2+ -CIZS QD complex, while the negative entropy contributes to the formation of the complex that decreases the chaos of the interaction system.…”
Section: Resultsmentioning
confidence: 99%
“…The probe FPS with excellent linear relationship for the Zn 2+ detection showed good and weak potential in imaging the exogenous and endogenous Zn 2+ , respectively, which can lead to the exploitation of growingly specific probes, particularly fluorescent for detection of Zn 2+ , Cu 2+ and diagnosis of Zn 2+ , Cu 2+ related diseases. In addition, the DFT calculations results showed how the structure affects the fluorescent behavior of FPS , which may help us to understand the essence of metal ions regulating effect in nature, and even give valuable reference to extend the real application of cell imaging ( Li et al, 2021 ), imaging-guided ( Sun et al, 2019 ), stimuli-responsive bioimaging ( Min et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%